2020
DOI: 10.31729/jnma.5147
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acute Kidney Injury in Patients with Liver Cirrhosis

Abstract: Introduction: Acute kidney injury is a common and life-threatening event in patients with liver cirrhosis occurring in approximately 20-50% of hospitalized patients of liver cirrhosis. Pre-renal acute kidney injury, the hepatorenal syndrome type of acute kidney injury and acute tubular necrosis represent the common causes. The aim of this study was to study the profile of acute kidney injury in patients with liver cirrhosis. Methods: Consecutive patients of liver cirrhosis admitted in Liver unit of Bir H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Renal failure was most prominent in CTP advanced-class B (21.9%), which is consistent with incidence reports in other studies. 16 Patients with more advanced LD were readmitted less frequently in comparison to CTP class A patients, which could be due to the higher mortality rate in CTP advanced-class B group. For both 30-day and in-hospital mortality, the observed overall mortality rate was surprisingly low (7.4%).…”
Section: Discussionmentioning
confidence: 92%
“…Renal failure was most prominent in CTP advanced-class B (21.9%), which is consistent with incidence reports in other studies. 16 Patients with more advanced LD were readmitted less frequently in comparison to CTP class A patients, which could be due to the higher mortality rate in CTP advanced-class B group. For both 30-day and in-hospital mortality, the observed overall mortality rate was surprisingly low (7.4%).…”
Section: Discussionmentioning
confidence: 92%
“…In a prospective study of 405 patients with cirrhosis enrolled in 2016-2017, the prevalence of AKI was 19.3%, and survival was lower at 30 d and 90 d compared to that of non-AKI patients[ 99 ]. The prevalence of AKI ranges from 18.5% to 40.6% in some other regions[ 100 - 102 ]. A meta-analysis revealed that the prevalence of AKI in acute-on-chronic liver failure (ACLF) could be significantly increased to 41%[ 103 ].…”
Section: Epidemiology Of Major Complicationsmentioning
confidence: 99%
“…Occurring in 40-50% of hospitalized patients, acute kidney injury (AKI) is a common complication in patients with advanced liver cirrhosis [1,2]. Numerous studies have established that kidney function plays a major role in the prognosis of cirrhosis [3].…”
Section: Introductionmentioning
confidence: 99%